The Effect of Cash Holdings and Solvency on Profitability: Multinational Companies Coal Production Subindustry Listed (IDX) - Djalalludin Akbar Akbar; Dava Indira Dandy; Syahla Nur Fikriyyah; Perwito Perwito (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Cash management in multinational companies is crucial for maintaining liquidity and optimizing profits. Currency differences are one factor driving companies to implement quality cash management to avoid losses caused by currency differences. The purpose of this study was to examine whether cash holdings and solvency can affect the profitability of multinational companies in the coal production sub-industry listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. The results showed that cash holdings did affect profitability, while solvency did not. Overall, the dependent variables simultaneously influenced the independent variables.